HUMANITY OF AN ARTIFICIAL LANGUAGE IN THE INFORMATION AGE CULTURE - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article aims to reveal human character of an artificial language in the Information Age culture.